Disparity Between One- and Two-Stage Factor VIII Assays in Measuring VIIIC in Heparinized Plasma - Rock, G; Palmer, D S (Thrombosis and Haemostasis, 1985)
The level of Factor VIII procoagulant activity (VIIIC) was found to be more than 30% higher in heparinized plasma than in citrated plasma from the same donor when determined by a one-stage assay (1.34 U/ml versus 1.0 U/ml). However, after Al(OH)3 adsorption and two-stage assay, the VIIIC levels were not significantly different for the two types of plasma (0.90 ± 0.25 U/ ml versus 0.82 ± 0.23 U/ml). If a one-stage assay was employed after adsorption, a similar low result was obtained (0.92 ± 0.21 U/ ml versus 0.91 ± 0.12 U/ml). This indicated that the adsorption step itself was responsible for the difference in results. Parallel analyses of other VIII markers demonstrated that more VIIIC antigen (VIIICAg) was removed by adsorption of heparinized rather than citrated plasma (0.33 U/ml versus 0.12 U/ml) although there was no difference in the level of VUI-related antigen (VIIIRAg). The results show that adsorption of heparinized plasma prior to either one- or two-stage assay leads to a greater loss of both VIIIC and VIIICAg activity than observed with citrated plasma and indicate that, when applied to heparin plasma the two-stage assay for VIIIC underestimates the actual VIIIC content.
Keywords: One- and two-stage assay of VIIIC; Adsorption of heparin plasma; Al(OH)3 effect on Factor VIII markers